Interplay between inherited rift faults and strike-slip structures: Insights from analogue models and field data from Iceland - Bonali, FL; Tibaldi, A; Pasquaré Mariotto, F; Russo, E (Global and Planetary Change, 2018)
Although structural inheritance is a fundamental factor in the tectonic evolution of the crust, few studies have been aimed at understanding in detail the interaction between pre-existing normal faults in a rift zone and successive dominant strike-slip (transtensional) movements. Firstly, we present the complex pattern of faults and tension fractures of the western, pre-Holocene part of the N-S Theistareykir Fissure Swarm (ThFS - Northern Iceland Rift), crossed by the NW-SE striking, right-lateral, Husavik-Flatey Fault (HFF), and we integrate previous observations with new field data that reveal Holocene motions along the N-S faults near the HFF. Secondly, we propose a set of analogue experiments that reproduce the N-S rifting followed by superimposed transtensional faulting along the HFF. In a first set of experiments, we tested the effect of an initial extension at the shallow crustal level by forming a rift zone. During this rifting phase, we modelled the presence of a sub-orthogonal discontinuity that represents the structural inheritance of the HFF (that is older than the ThFS), but without any imposed “regional” transtensional movement along it. After that, we superimposed a dominant right-lateral movement along the HFF on the modelled rift faults in order to assess the effect of the inheritance of the rift plus the HFF. Our results show that during rifting, a series of elongated and depressed areas develop along the initial HFF discontinuity (that is locally reactivated by the rift opening), in agreement with field data. During the second experimental set of exclusively shear deformation along the HFF, the models show the development of Riedel shears at the HFF, contemporaneous to the local reactivation of normal faults and tension fractures in the previous rift zone. This reactivation occurs by block rotation, incremental dip-slip motions on pre-existing fault scarps, widening of tension fractures and development of new structures. We conclude that transversal basins can develop from the early stages of ...